Nuclease Activity of Saccharomyces cerevisiae Mre11 Functions in Targeted Nucleotide Alteration - Liu, Li (American Society for Microbiology, 2003)
Oligonucleotides can be used to direct site-specific changes in genomic DNA through a process in which mismatched base pairs in the oligonucleotide and the target DNA are created. The mechanism by which these complexes are developed and resolved is being studied by using Saccharomyces cerevisiae as a model system. Genetic analyses have revealed that in all likelihood the reaction occurs in two phases: DNA pairing and DNA repair. While the former phase involves strand assimilation, the latter phase likely involves an endonucleolytic processing step that leads to joint resolution. In this study, we established the importance of a functioning MRE11 gene in the overall reaction, as yeast strains deficient in MRE11 exhibited severely reduced activity. The activity could be rescued by complementation with wild-type MRE11 genes but not with MRE11 alleles lacking the nuclease function. Taken together, the data suggest that Mre11 provides nuclease activity for targeted nucleotide exchange, a process that could be used to reengineer yeast genes.